1999
DOI: 10.1038/sj.mp.4000473
|View full text |Cite
|
Sign up to set email alerts
|

Environment and vulnerability to major psychiatric illness: a case control study of early parental loss in major depression, bipolar disorder and schizophrenia

Abstract: The current focus on identifying genes which predispose to psychiatric illness sharpens the need to identify environmental factors which interact with genetic predisposition and thus contribute to the multifactorial causation of these disorders. One such factor may be early parental loss (EPL). The putative relationship between early environmental stressors such as parental loss and psychopathology in adult life has intrigued psychiatrists for most of this century. We report a case control study in which rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
342
1
10

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(372 citation statements)
references
References 40 publications
19
342
1
10
Order By: Relevance
“…It has consistently been reported that psychosis is associated with a wide range of early adverse experiences . Some of these experiences of parental separation (Agid et al, 1999) neglect Sitko et al, 2014) victimisation through means of sexual abuse (Read et al, 2005), and of being unwanted at birth (Myhrman et al, 1996) may result in disruptions to the development of early secure attachment relationships, and may subsequently lead to the development of incoherent self/others beliefs that fluctuate over time.…”
Section: Discussionmentioning
confidence: 99%
“…It has consistently been reported that psychosis is associated with a wide range of early adverse experiences . Some of these experiences of parental separation (Agid et al, 1999) neglect Sitko et al, 2014) victimisation through means of sexual abuse (Read et al, 2005), and of being unwanted at birth (Myhrman et al, 1996) may result in disruptions to the development of early secure attachment relationships, and may subsequently lead to the development of incoherent self/others beliefs that fluctuate over time.…”
Section: Discussionmentioning
confidence: 99%
“…This seminal observation was subsequently confirmed in a large number of epidemiological, twin and case-control studies demonstrating that loss of a parent due to death or separation increases the risk for major depression in adulthood (Agid et al, 2000). Early loss experience (ELE) was also found to predispose for a variety of other psychiatric disorders, including bipolar disorder, anxiety disorders, schizophrenia, and alcohol abuse (Agid et al, 1999;Kendler et al, 1992Kendler et al, , 2002a. There is also evidence for a relationship between ELE and physical illnesses, functional somatic syndromes and several health risk behaviors (Lowman et al, 1986;Felitti et al, 1998;Agid et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Early loss experience (ELE) was also found to predispose for a variety of other psychiatric disorders, including bipolar disorder, anxiety disorders, schizophrenia, and alcohol abuse (Agid et al, 1999;Kendler et al, 1992Kendler et al, , 2002a. There is also evidence for a relationship between ELE and physical illnesses, functional somatic syndromes and several health risk behaviors (Lowman et al, 1986;Felitti et al, 1998;Agid et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood abuse has also been associated with earlier-onset and more chronic depression ). In addition, parental loss predominantly due to parental separation has also been found to increase the risk for major depression in casecontrol and epidemiological studies (Agid et al, 1999). Twin studies have provided concordant findings (Kendler et al, 1992(Kendler et al, , 1993(Kendler et al, , 2002.…”
Section: Evidence For a Role Of Els In The Pathophysiology Of Depressmentioning
confidence: 99%